Vancomycin vs teicoplanin in the treatment of Gram-positive infections: a pharmacoeconomic analysis in a Turkish University Hospital - (:unkn) unknown (SPRINGER, 2008)
Objective The aim of this study was to estimate and compare the costs of vancomycin and teicoplanin in the treatment of Gram-positive hospital infections in Turkey using a cost minimisation analysis. Setting Hacettepe University Hospital, Ankara, Turkey. Method The health-care provider's perspective was considered within formal pharmacoeconomic assessment methodology. The records of 76 patients who had been hospitalised and treated for Gram-positive infections at Hacettepe University Hospital between 16 July 2003 and 22 November 2003 were retrospectively evaluated to obtain individual data on resources and associated costs. Main outcome measure From a cost minimisation perspective, hospital directors may consider teicoplanin to be a relevant option in addition to vancomycin. Result The estimated mean treatment cost per patient was 1,780 TRY (1,101 EUR) for teicoplanin and 1,429 TRY (884 EUR) for vancomycin, with statistical analysis failing to reveal any significant difference between the two drugs in terms of these total costs (p = 0.33). This cost minimisation analysis shows that the average costs of vancomycin and teicoplanin per patient observed did not differ significantly. Conclusion Other potential advantages of one drug over the other, as reported by other authors, such as differing safety profiles or advantages in administration, may ultimately decide which is preferred.
Keywords: Cost minimisation analysis; Glycopeptide; Pharmacoeconomics; Teicoplanin; Turkey; Vancomycin; FEBRILE NEUTROPENIA; COST-EFFECTIVENESS; EMPIRIC THERAPY; EFFICACY; SAFETY